Sosialisasi Pemanfaatan Teknologi Sensor Air Bersih pada Desa Tanggap Bencana Longsor - Purwono Purwono; Khoirun Nisa; Bala Putra Dewa; Sony Kartika Wibisono (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
Tlaga Village is one of the areas prone to landslides in Banyumas Regency. This village has experienced emergency situations because parts of its area have experienced landslides and caused various losses, both material and non-material. Every rainy season, this area is always threatened by landslides. The need for clean water in this village is quite difficult, especially when landslides occur. The location of this village is in the form of a plateau, so access to clean water is difficult, especially if an avalanche occurs. The quality of the water available during the rainy season is also quite dirty, which has a negative impact on public health. Based on these problems, the use of technology is proposed to ensure the basic need for clean water in disaster-prone areas. This community service utilizes technology such as internet-based products for mapping clean springs to measuring water quality. Mapping of springs is useful for facilitating the community in maintaining and supplying water. Clean water measurements such as the use of water quality technology sensors are also useful to make it easier to know the quality of water properly. Communities have received socialization to deal with the possibility of landslides which have an impact on the difficulty of access to clean water